Effects of marital closeness on the transition from caregiving to widowhood - Pruchno, Rachel A. (Aging Ment Health, 2009)
OBJECTIVE: To examine the effects of marital closeness on indicators of well-being (depressive symptoms, grief, and relief) as spouses transition from the role of caregiver to that of widowed person. METHODS: 118 spouses of persons with end stage renal disease were interviewed prior to and after the death of the patient. Spouses reported on marital closeness, multiple indicators of pre-death strain as reflected by subjective health, depressive symptoms, caregiving burden, and caregiving satisfaction, as well as post-loss feelings of grief, depression, and relief. RESULTS: Hierarchical regressions indicated that post-loss grief was predicted by gender (b = −0.32, p < 0.001), self-reported health (b = −0.28, p < 0.01), marital closeness (0.22, p < 0.05), and pre-loss depressive symptoms (b = 0.19, p < 0.10). Caregiver burden (b = 0.28, p < 0.05) and marital closeness (b = −0.41, p < 0.001) before the death, predicted relief from the caregiver role post-loss. Subjective health (b = −0.21, p < 0.05) and pre-loss depressive symptoms (b = 0.47, p < 0.001) predicted change in depressive symptoms over time. CONCLUSION: These data highlight differences in the experiences of grief, relief, and depressive symptoms and suggest that marital closeness plays a central role. Results are interpreted in terms of theory regarding marital quality. Implications for interventions to improve the lives of caregivers and newly widowed spouses are discussed.